Employee Safety Measures as a Means for Enhancing Occupational Health among Casual Laborers in the Manufacturing Industries of Lira City, Uganda - Auma, Morine; Okuna, Victor; Mwesigwa, David (Human Resource and Leadership Journal, 2024)
Purpose: Occupational health remains a public health concern worldwide and given that occupational health hazards are disproportionately high among casual workers in the manufacturing industry, this study aimed to assess the efficacy of employee safety measures on the occupational health of casual workers in the manufacturing industries of Lira City. Methodology: This study employed a descriptive cross-sectional research design using quantitative methods to assess and describe the efficacy of employee safety measures on occupation health of casual workers in Mt. Meru Millers, which is an Agri-processing company dealing mainly in processing of Soya, Sunflower, among other agricultural products into oil, soap, fuel and animal feeds. A sample size of 58 respondents was reached using semi-structured questionnaires. Also, a univariate logistic regression test was used to estimate the bivariate level of association between the dependent and independent variables. Findings: The results revealed that majority of the respondents (60.8%) reported to have experienced work-related accidents caused by chemical reactions (49.0%), machines (33.3%), sharp objects and falls. The overall occupation health of casual workers in Mt. Meru millers was poor with the biggest occupational health problem being disruption of social relationships as well as violation of workers’ ethical, moral and cultural values. Unique contribution to theory, practice and policy: This study contributes to the understanding of occupational health risks and hazards affecting majorly the low-level laborers who contribute much to the global manufacturing industry (especially those that are still relying on crude methods of production) despite being less-valued by a number of industrialists.